A risk stratification scoring system for new-onset atrial fibrillation after ischemic stroke: A National cohort study. Issue 27 (2nd July 2020) - Chen, Yung-Lung; Wang, Hui-Ting; Chen, Huang-Chung; Liu, Wen-Hao; Hsueh, Shukai; Chung, Wen-Jung; Wu, Po-Jui; Liu, Chi-Hung; Chung, Chang-Ming; Lin, Yu-Sheng
Abstract : Abstract: Atrial fibrillation (AF) is a major independent risk factor of stroke and anticoagulation therapy is needed in patients with AF after ischemic stroke. However, the detection rate of AF is low after ischemic stroke. Developing a prediction model for newly diagnosed AF after ischemic stroke will help to assess the subclinical AF. We identified 98, 103 patients with diabetes mellitus (DM) and 261, 893 patients without DM, who were not AF history and admitted for newly ischemic stroke from the National Health Insurance Research Database in Taiwan. The prediction model for 3-year incidence of AF after ischemic stroke was derived from multivariate logistic regression and also the accuracy rate of the prediction model was compared with CHA2 DS2 -VASC and CHADS2 scores as a reference. Four thousand nine hundred seventy six patients in the DM cohort and 16, 127 patients in the non-DM cohort developed AF during 3 years of follow-up. The variables in the point-based prediction model for non-DM patients (range: -3–28), included age, heart failure, coronary artery disease, gout, obstructive pulmonary disease, hypertension, female, and statin use, while those for DM patients (range: -2–30) included age, heart failure, coronary artery disease, chronic kidney disease, hypertension, obstructive pulmonary disease, and statin use. Compared to the CHADS2 and CHA2DS2-VASc scoring systems, this scoring system was better at predicting 3-year risk of AF after ischemic stroke in both cohorts. This model might be useful in evaluating the benefit of insertable cardiac monitor implantation and anticoagulation agents in individual patients after ischemic stroke. Abstract : Supplemental Digital Content is available in the text